Կաղամբի տերևակեր վնասատուների դեմ պայքարի միջոցառումների մշակում ըստ Bacillus thuringiensis տեսակի բակտերիական շտամների չափագրական ցուցանիշների - Թերլեմեզյան, Հրանտ; Սարգսյան, Մասիս; Հարությունյաn, Հարություն; Սարգսյան, Սոնա (ՀԱԱՀ հիմնադրամ)
Из отдельных компонентов биоценоза микробиологическим способом выделены два штамма бактериальных инсектицидов вида Bt и изучены метрические показатели их вегетативных клеток, эндоспор, кристаллов, бактериальных колоний, сформированных на питательной среде МПА. Научными экспериментами подтверждено, что в борьбе с гусеницами капустной белянки эффективно раздельное использование культуральных жидкостей BtHm07 иBtLd88 с титром 300 млн спор/мл, а против капустной совки – сочетания инсектицидов BtHm07 с титром 600 млн спор/мл + Амплиго (0.006 %), BtLd88 с титром 600 млн спор/мл + Амплиго (0.006 %). In 2019-2023, two insecticidal strains of the Bt species were microbiologically isolated from individual components of the biocenosis, and measured values of their vegetative cells, endospores, insecticidal crystallophores, and bacterial colonies formed on a nutrient medium of MPA were revealed. Culture fluids BtHm-07 and BtLd-88 were tested on cabbage plantings separately with a titer of 300 million spores/ml against caterpillars of the II - III ages of cabbage white butterfly, and combinations of culture fluids (titer of 600 million spores/ml) + sub-lethal concentration of ampligo (0.006 %) – against caterpillars of the I - II ages of cabbage scoops were investigated. High biological efficiency was noted in the tested variants. Microbiological examination confirmed that the decomposed tissues of the dead larvae in the experimental versions were saturated (full) with Bt bacterial insecticides (vegetative cells, also formed by spore-crystal components), the presence of which confirmed that the mortality of the larvae was the result of the effect of the insecticidal bacteria. Statistical analysis confirmed that there is no credible difference between the biological efficiency indicators shown in the experimental and standard versions. The experimental error and coefficient of variation indicators confirm that the results of scientific experiments are accurate.
Keywords: Ագրոնոմիա